Treatment of SARS-CoV-2 with high dose oral zinc salts: A report on four patients. (October 2020) - Finzi, Eric
Highlights: Treatment of COVID-19 with high dose zinc salts Improvement of oxygenation in COVID-19 after zinc gluconate Rapid resolution of COVID-19 shortness of breath after zinc salts Abstract: Coronavirus 2019 (COVID-19) is a pandemic with substantial mortality and no accepted therapy. We report here on four consecutive outpatients with clinical characteristics (CDC case definition) of and/or laboratory-confirmed COVID-19 who were treated with high dose zinc salt oral lozenges. All four patients experienced significant improvement in objective and symptomatic disease measures after one day of high dose therapy suggesting that zinc therapy was playing a role in clinical recovery. A mechanism for zinc's effects is proposed based on previously published studies on SARS- CoV-1, and randomized controlled trials assessing zinc shortening of common cold duration. The limited sample size and study design preclude a definitive statement about the effectiveness of zinc as a treatment for COVID-19 but suggest the variables to be addressed to confirm these initial findings in future trials.